PENGARUH KOMPENSASI DAN KOMITMEN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. SEMEN INDONESIA UNIT TONASA DI KABUPATEN PANGKEP - Thoriq Khatam Alamsyah; Romansyah Sahabuddin; Ahmad Ali; Zainal Ruma; Uhud Darmawan Natsir (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of compensation, work commitment on employee job satisfaction, this study uses primary data obtained by distributing questionnaires to the managers of PT. Semen Indonesia (Persero) Unit Tonasa with a population of 138 people and a sample of 103 people. The multiple analysis method using the SPSS application used in this study is an instrument test. This study used a quantitative approach and was analyzed using multiple linear regression analysis with the help of SPSS 25 data processing to prove three hypotheses. The results of this study prove that the compensation variable has a significant effect on job satisfaction, t count > ttable, which is 3.195 > from T table of 1.983. The commitment variable has a significant effect on job satisfaction because the tcount > ttable is where 2.916 > 1.983. Based on the results of this study it is also known that the independent variables jointly or simultaneously have a significant effect on the dependent variable, namely the performance of employees at PT. Semen Indonesia Unit Tonasa in Pangkep Regency. Therefore, if work motivation and compensation continue to be improved, then of course it will improve employee performance to be more optimal.